PENGEMBANGAN MODUL AJAR BERBASIS PEMBELAJARAN BERDIFERENSIASI DALAM MATERI STATISTIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA SMP - Nadika Susiani; Yudi Darma; Rahman Haryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop a teaching module based on differentiated learning in statistics material to enhance problem-solving skills that can achieve levels of validity, practicality, and effectiveness. This research is a type of Research and Development (R&D) study using the ADDIE development model. The instruments used to collect data are the validation sheet for learning devices, the validation sheet for LKPD, the teacher response questionnaire, the student response questionnaire, and the post-test. Based on the first research results, the calculation of the validation sheet for the learning device (teaching module) is 82.42% and the LKPD is 85.19%, each with very valid criteria. The average calculation of the validation sheet results is 83.81%, which indicates a very valid criterion. The second practicality score, based on the teacher response questionnaire and the student response questionnaire, with an average value of 85.51%, falls into the very practical category. As for the third aspect, the effectiveness of the differentiated learning-based teaching module in statistics on the problem-solving abilities of junior high school students reached 67.24%, which falls into the effective category, based on the posttest assessment results.